Dominance of legume trees alters nutrient relations in mixed species forest restoration plantings within seven years - Siddique, Ilyas; Engel, Vera Lex [UNESP]; Parrotta, John A.; Lamb, David; Nardoto, Gabriela B.; Ometto, Jean P. H. B.; Martinelli, Luiz A.; Schmidt, Susanne (Springer, 2008)
Failures in reforestation are often attributed to nutrient limitation for tree growth. We compared tree performance and nitrogen and phosphorus relations in adjacent mixed-species plantings of contrasting composition, established for forest restoration on Ultisol soil, originally covered by tropical semi-deciduous Atlantic Forest in Southeast Brazil. Nutrient relations of four tree species occurring in both planting mixtures were compared between a legume-dominated, species-poor direct seeding mixture of early-successional species ("legume mixture"), and a species-diverse, legume-poor mixture of all successional groups ("diverse mixture"). After 7 years, the legume mixture had 6-fold higher abundance of N(2)-fixing trees, 177% higher total tree basal area, 22% lower litter C/N, six-fold higher in situ soil resin-nitrate, and 40% lower in situ soil resin-P, compared to the diverse mixture. In the legume mixture, non-N(2)-fixing legume Schizolobium parahyba (Fabaceae-Caesalpinioideae) had significantly lower proportional N resorption, and both naturally regenerating non-legume trees had significantly higher leaf N concentrations, and higher proportional P resorption, than in the diverse mixture. This demonstrate forms of plastic adjustment in all three non-N(2)-fixing species to diverged nutrient relations between mixtures. By contrast, leaf nutrient relations in N(2)-fixing Enterolobium contortisiliquum (Fabaceae-Mimosoideae) did not respond to planting mixtures. Rapid N accumulation in the legume mixture caused excess soil nitrification over nitrate immobilization and tighter P recycling compared with the diverse mixture. The legume mixture succeeded in accelerating tree growth and canopy closure, but may imply periods of N losses and possibly P limitation. Incorporation of species with efficient nitrate uptake and P mobilization from resistant soil pools offers potential to optimize these tradeoffs.
Keywords: native tree plantations; nodulating multi-purpose trees; nutrient retranslocation; soil nitrate; stand nitrogen accrual; tropical forest restoration